Harnessing the Power of Low-tech Collaborative Learning. Issue 6 (17th July 2020) - Sheth, Monica; Samreen, Naziya; Rapoport, Irina; Slanetz, Priscilla J; Fornari, Alice; Lewis, Petra
Abstract: Medical education in the United States has undergone a paradigm shift from passive learning to more interactive student-centered teaching methods. Several digital tools and platforms have been developed to assist educators in creating a high-tech, interactive classroom. However, there are many low-tech ways to engage learners and improve retention by combining collaborative learning techniques and summary exercises. Collaborative learning is an educational approach that involves the coordinated engagement of two or more learners for the purpose of completing a task or solving a problem. Such methods use a student-centered active learning model to promote higher-order cognitive tasks through active engagement in course content. Additionally, summary exercises at the end of a learning activity promote reflection and retention of learned concepts while clarifying content that may have been confusing for the learner. The purpose of this article is to describe the methodology and tips for the implementation of low-tech collaborative learning methods and summary activities into trainee educational activities to create an engaging student-centered learning environment. Graphical Abstract: